Organizational change: challenges for workplace psychosocial risks and employee mental health - Insa Backhaus; Andrea Lohmann-Haislah; Hermann Burr; Karina Nielsen; Cristina di Tecco; Nico Dragano (BMC, 2024)
Abstract Background Constant organizational change is the norm in many companies today. At present, evidence on the impact of organizational change on psychosocial risks at work and employee mental health is limited. We investigate organizational change and its association with psychosocial risks and mental health in three consecutive surveys covering 12 years. Methods The study was based on data from three cross-sectional waves (2006, 2012, 2018) of the German BIBB/BAuA Employment Survey, comprising 53,295 employees. Four change indicators (i.e., introduction of new software, changes in goods and services produced/provided, downsizing and restructuring), five indicators of psychosocial risks (i.e., time pressure, interruptions, multitasking, working to the limits of capability, and working very quickly) and four mental health indicators (i.e., sleep disturbances, nervousness, tiredness and depressive symptoms) were investigated. We applied Poisson regression analysis to examine associations between organizational change, psychosocial risks, and mental health. Results According to the pooled analysis of all three waves, the majority of employees reported having experienced at least one organizational change, such as downsizing or restructuring, between 2006 and 2018. Organizational change was negatively associated with psychosocial risks (e.g., working to the limits of one's capability, PR: 1.66; 95% CI: 1.48-1.86) and with employee mental health (PR: 1.82; 95% CI: 1.61-2.04). Conclusions Organizational change is omnipresent in the modern economy. Our research suggests that transformation processes in organizations can bear risks to employees' health as psychosocial risks increase. Therefore, companies planning organizational change should accompany such processes with occupational health and safety measures.